Effectiveness of Acupressure Therapy as a Complementary Approach in Pain Management of Cervical Cancer Patients - Purnama, Safik Setia; Ningrum, Ema Wahyu (International Journal Of Health Science, 2025)
Pain is one of the most common and distressing symptoms experienced by patients with cervical cancer. It significantly affects patients’ quality of life, leading to both physical and psychological burden. Conventional pharmacological interventions often come with side effects and may not fully address the multidimensional nature of pain. As an alternative, non-pharmacological approaches such as acupressure therapy have gained attention for their potential effectiveness and minimal risk profile. Acupressure is a form of traditional Chinese medicine that involves applying manual pressure to specific points on the body to stimulate healing and relieve discomfort. This case study highlights the outcome of a three-day acupressure intervention administered to a cervical cancer patient suffering from moderate pain and anxiety. Before the intervention, the patient’s pain level was recorded at a score of 4, accompanied by noticeable anxiety. Following consistent acupressure sessions, both the pain and anxiety scores decreased to 2, indicating a meaningful improvement in comfort and emotional state. The underlying mechanism of acupressure is believed to involve the stimulation of the central nervous system, which enhances the release of endorphins—natural painkillers that act as analgesics. These findings suggest that acupressure not only provides symptomatic relief but also contributes to emotional well-being, making it a viable complementary therapy for cancer pain management. While this case study offers promising results, it is limited by its single-subject design. To validate these outcomes, further research using a randomized controlled trial (RCT) methodology and a larger sample size is highly recommended. This will provide more robust evidence on the efficacy of acupressure and support its integration into holistic cancer care.